PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP PERINGKAT OBLIGASI PERUSAHAAN DI INDONESIA - Agung Edy Wibowo; Linawati Linawati (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2020)
Investors attempted to optimize the level of profit from the capital invested in the company. Bond rating can be used by investors to predict whether a bond able to attract investors to buy it or not through the liquidity, profitability and leverage assessment approaches of a bond. This study aimed to analyze the effect of Liquidity, Profitability and Leverage on Company Bond Ratings in Indonesia. This field research was used cross section data. The research objects used were all banking, financing and insurance industry companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The results showed that return on assets has no significant effect on bond rating predictions. Return on equity does not have a significant effect on bond ratingpredictions. Debt to assets significantly influences the prediction of bond ratings. Debt to equity has a significant effect on bond rating predictions.